PENGARUH METODE PAIKEM TERHADAP KEMAMPUAN MEMBUAT TEKS PUISI - Rian Pratama; Indra Permana (IKIP Siliwangi, 2019)
This research is in the background of the existence of data from the evaluation results on the writing skills of students in class XI tends to be still low. This is caused by the selection of learning models so that students are less motivated and lack interest in the learning done. Because of these problems, the researchers conducted a study of poetry text learning using the PAIKEM learning model. and the thing to be investigated in an attempt to find out whether the learning process has different results before and after using the PAIKEM learning model. The researcher used the Design One-Group pretest-posttest Design method, the researcher used the subject as a sample of 25 students. Researchers research by conducting a pretest as the beginning of learning and doing a posttest. Based on the results of the pretest conducted by students obtained an average value of 50.8 and obtained an average posttest score of 86 so that it can have a difference in the value of 32.2.